KEPEMIMPINAN PENDIDIKAN ISLAM PERSPEKTIF SUKU - Widya Hastuti; Siti Munawwaroh; Feni Husnul Fatimah; Ansori Ansori; Iwan Aprianto (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRACT Islamic educational leadership plays a crucial role in directing and managing educational institutions to achieve educational goals oriented toward the intellectual, moral, and spiritual development of learners. Within Indonesia's multicultural society, leadership practices in Islamic education are influenced by cultural values and local wisdom embedded in diverse ethnic communities. This study aims to analyze the concept of Islamic educational leadership from an ethnic perspective, identify the forms of integration between Islamic values and local cultural values, and explain their implications for the administration of Islamic educational institutions. This study employed a qualitative approach using the library research method. Data were collected from books, scientific journal articles, research reports, and other relevant academic documents, and were analyzed using content analysis through the stages of data reduction, data presentation, interpretation, and conclusion drawing. The findings reveal that Islamic leadership principles, including trustworthiness (amanah), justice, consultation (shura), exemplary conduct, and responsibility, are closely aligned with the leadership values found in various Indonesian ethnic traditions, such as mutual cooperation (gotong royong), social solidarity, togetherness, and respect for customary traditions. The integration of these values produces a conceptual leadership model that is religious, contextual, participatory, and adaptive to multicultural communities. This study concludes that Islamic educational leadership based on an ethnic perspective has the potential to strengthen character education, enhance the effectiveness of educational governance, and serve as an alternative leadership model that preserves both Islamic values and local wisdom in the face of globalization. ABSTRAK Kepemimpinan pendidikan Islam memiliki peran penting dalam mengarahkan dan mengelola lembaga pendidikan untuk mencapai tujuan pendidikan yang berorientasi pada pengembangan intelektual, moral, dan spiritual peserta didik. Dalam masyarakat Indonesia yang multikultural, praktik kepemimpinan pendidikan dipengaruhi oleh nilai-nilai budaya dan kearifan lokal yang berkembang dalam berbagai kelompok suku. Penelitian ini bertujuan menganalisis konsep kepemimpinan pendidikan Islam dalam perspektif suku, mengidentifikasi bentuk integrasi nilai-nilai Islam dengan budaya lokal, serta menjelaskan implikasinya bagi penyelenggaraan lembaga pendidikan Islam. Penelitian menggunakan pendekatan kualitatif dengan metode library research. Data diperoleh dari buku, artikel jurnal ilmiah, hasil penelitian, dan dokumen akademik yang relevan, kemudian dianalisis menggunakan teknik content analysis melalui tahapan reduksi data, penyajian data, interpretasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa prinsip kepemimpinan Islam, seperti amanah, keadilan, musyawarah, keteladanan, dan tanggung jawab, memiliki keselarasan dengan nilai-nilai kepemimpinan berbagai suku di Indonesia, seperti gotong royong, solidaritas, kebersamaan, dan penghormatan terhadap adat. Integrasi tersebut menghasilkan model konseptual kepemimpinan yang religius, kontekstual, partisipatif, dan adaptif terhadap masyarakat multikultural. Penelitian ini menyimpulkan bahwa kepemimpinan pendidikan Islam berbasis perspektif suku berpotensi memperkuat pendidikan karakter, meningkatkan efektivitas pengelolaan lembaga pendidikan, serta menjadi alternatif pengembangan kepemimpinan yang mampu menjaga nilai-nilai keislaman dan kearifan lokal di tengah tantangan globalisasi.